2016
DOI: 10.1039/c5ta08170j
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide sensing using tungsten oxide microspheres with hierarchical nanorod-assembled architectures by a complexing surfactant-mediated hydrothermal route

Abstract: WO3 microspheres with hierarchical nanorod-assembled architectures were synthesized by a complexing surfactant-mediated hydrothermal method and showed high-performance NO2 sensing properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The comparison of present study along with responses observed by other researchers using different nanostructures of WO 3 is shown in Table 1. [42][43][44][45][46][47][48][49][50][51] The present study on the WO 3 thin lm-based NO 2 sensor concludes that sub-ppb level NO 2 detection with high sensitivity and selectivity can be obtained by simple reactive-ion sputtered technique, a scalable process. The WO 3 lm selectivity towards NO 2 was tested in the presence of CO, CO 2 , SO 2 , and NH 3 gases at 150 C. The study clearly indicates the high selectivity of the lm towards NO 2 among other gas species, as represented in Fig.…”
Section: Nitrogen Dioxide (No 2 ) Sensing Characteristics Of the Wo 3mentioning
confidence: 62%
“…The comparison of present study along with responses observed by other researchers using different nanostructures of WO 3 is shown in Table 1. [42][43][44][45][46][47][48][49][50][51] The present study on the WO 3 thin lm-based NO 2 sensor concludes that sub-ppb level NO 2 detection with high sensitivity and selectivity can be obtained by simple reactive-ion sputtered technique, a scalable process. The WO 3 lm selectivity towards NO 2 was tested in the presence of CO, CO 2 , SO 2 , and NH 3 gases at 150 C. The study clearly indicates the high selectivity of the lm towards NO 2 among other gas species, as represented in Fig.…”
Section: Nitrogen Dioxide (No 2 ) Sensing Characteristics Of the Wo 3mentioning
confidence: 62%
“…Tungsten oxide synthesized from PTA + EtOH sol-gel has much sharper peaks due to a more orderly structure with well-expressed W-O stretching vibration. The broad band at 3400 cm −1 can be attributed to W-OH stretching vibration, and the peak located at 1625 cm −1 corresponds to W-OH bending vibration mode of the adsorbed water molecules [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The small peak at 41.5 eV can be attributed to the W 5p 3/2 of WO 3 [17,33]. The two evident peaks at 35.5 and 37.7 eV, belonging to W 4f 7/2 and W 4f 5/2 of WO 3 , respectively, suggest that the tungsten oxide nanostructure exists as W 6+ [34][35][36].…”
Section: Materials Characteristicsmentioning
confidence: 91%
“…The electron depletion theory is well known to explain gas-sensing mechanisms by charge transfer between gas molecules and sensing materials [36,45]. Figure 9 shows the schematic diagram of NO 2 -sensing mechanism for WO 3 nanomesh sensor.…”
Section: Gas Sensing Mechanismmentioning
confidence: 99%